American Cancer Society, American Society for Colposcopy and Cervical Pathology, and American Society for Clinical Pathology Screening Guidelines for the Prevention and Early Detection of Cervical Cancer. Issue 4 (August 2015) - Saslow, Debbie; Solomon, Diane; Lawson, Herschel W.; Killackey, Maureen; Kulasingam, Shalini L.; Cain, Joanna; Garcia, Francisco A. R.; Moriarty, Ann T.; Waxman, Alan G.; Wilbur, David C.; Wentzensen, Nicolas; Downs, Levi S.; et al.
Abstract : An update to the American Cancer Society (ACS) guideline regarding screening for the early detection of cervical precancerous lesions and cancer is presented. The guidelines are based on a systematic evidence review, contributions from 6 working groups, and a recent symposium cosponsored by the ACS, the American Society for Colposcopy and Cervical Pathology, and the American Society for Clinical Pathology, which was attended by 25 organizations. The new screening recommendations address age-appropriate screening strategies, including the use of cytology and high-risk human papillomavirus (HPV) testing, follow-up (eg, the management of screen positives and screening intervals for screen negatives) of women after screening, the age at which to exit screening, future considerations regarding HPV testing alone as a primary screening approach, and screening strategies for women vaccinated against HPV16 and HPV18 infections.